Global analysis of tetanus incidence and mortality in children under 5 years: findings from the Global Burden of Disease Study 2021 - Li He; Cheng Liu; Jiangshan He; Xianli Nie; Dachuan Deng; Wenlai Zhou; Xiangde Zheng (BMJ Paediatrics Open)
Background Understanding trends in the incidence and mortality of tetanus in infants and young children is essential to develop prevention and intervention strategies.Methods Data on tetanus incidence and mortality among children aged under 5 years from 1990 to 2021 were obtained from the Global Burden of Disease Study 2021. Estimated annual percentage changes were calculated to assess the trends in the change of children’s tetanus incidence and mortality and the burden of disease. The relationship between disease burden and Sociodemographic Index (SDI) was also analysed.Results Globally, the incidence of children’s tetanus decreased from 308 931 cases in 1990 to 17 788 cases in 2021. Similarly, tetanus mortality among children has decreased significantly over the past 30 years, from 24.62 per 100 000 to 1.34 per 100 000, with little gender difference observed. The highest rates were seen in the Caribbean, Central Sub-Saharan Africa, Eastern Sub-Saharan Africa, North Africa and the Middle East, South Asia, Southeast Asia and Western Sub-Saharan Africa. The incidence and mortality of tetanus in children are significantly different in areas with different SDI levels. The incidence and mortality in areas with low SDI are higher than those in areas with high SDI.Conclusion The incidence and mortality of tetanus in children have decreased to varying degrees worldwide, but they are still high in some regions, especially in countries with low SDI, which highlights the impact of socioeconomic factors on the outcome of the disease. More targeted supportive measures are imperative for mitigating the global burden posed by children’s tetanus.